Efek Pupuk Kandang Dan Jamur Trichoderma harzinum Terhadap Penyakit - Fatimah, Fatimah (Jurnal Embrio, 2008)
The effect maneer fertilizer and Trichoderma harzinum fungus to damping-off diseases on chili seedling. The research was conduced from Mai 2004 to September 2004 in Balai Proteksi Tanaman Pangan and Horticultura Wilayah II West Sumatera, Riau, and Jambi and greenhause of the Faculty of Agriculture University of Tamansisa Padang. Experiment methodology using Completely Randomized Design in factorial with 3 replication, the first factor was kind of maneer fertilizer (A) : without maneer fertilizer (A0) maneer fertilizer from cow (A1), maneer fertilizer from chiken (A2), maneer fertilizer from hors (A3). The second factor was Trichoderma harzianum (B) Consisting of two treatment level : Without (B0) Inoculated Trichoderma harzianum(B1). Parameter was appear symptom firsly, persentase attack and population Rhizoctonia solani fungus and population Trichoderma harzianum fungus. The result of experiment showed that combination maneer from cow and inoculated Trichoderma harzianum are the best influence to suppress the disease of damping-off on chili seedling.